THE CRITERIA OF PROCESS OF FORMATION OF VALUABLE BELIEF OF THE FUTURE MUSICIAN-TEACHER (Pedagogy of Higher and Secondary Education, 2007)
The problem of valuable belief of the future musicians-teachers is considered in the article. The criteria cof process of formation of valuable belief are defined there with the purpose of their effective usage in teaching and educational process.
Keywords: valuable belief; musician-teacher; criteria of formation of valuable belief